PERSEPSI MASYARAKAT TERHADAP PERKEMBANGAN INDUSTRI MEUBEL DI DESA LEILEM KECAMATAN SONDER KABUPATEN MINAHASA - Claudia Mega Pajow; Oktavianus Porajow; Ellen Grace Tangkere (AGRI-SOSIOEKONOMI, 2020)
This study aims to analyze people's perceptions of the development of the furniture industry in Leilem Village, Sonder District. Community perception is very important to be able to foster active communication so that the development of the furniture industry in the village of Leilem continues to experience an increase in the type of furniture and its quality. This study uses primary data obtained through direct interviews with 30 respondents using a questionnaire to the community of Leilem Village, Sonder District using a simple random sampling method. The analysis used in this study was to use a Likert Scale analysis. The results showed that the index of public perception of the development of the furniture industry was at a point of 95.1% so it was classified as high. The development of the furniture industry is very influential for the survival of the community. A good industry is an opportunity for people to depend their lives on the results of the furniture industry.*eprm*